Therapy Emotional Freedom Techniq (EFT) Plus Music on Increasing the Self-Price of Skizofrenia Patients in RSJD Dr. Amino Gondohutomo Central Java Province - Yosina Atanai (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Soul problems are one of the four major health problems in developed and modern countries. In Indonesia, mental nursing therapy is used more using the psychotherapy approach with complementary therapy. Complementary therapies provide healing techniques that are relatively fast, easy and not at high risk. One of them is Emotional Freedom Technique (EFT) Plus Music, that is a form of complementary therapy which is one variant of the new branch of psychology called Energy Psychology. Method The type of research used is research Quasy Experimental with a pretest-posttest control group design. This study compiled two groups, namely the intervention group and the control group. Technique Non-probability sampling with method was pusposive sampling used to get 32 respondents divided into 2 groups. Results The results of the test Mann Withney show values p value 0.001 so that there is a difference in the self-esteem of schizophrenic respondents between the intervention group and the control group. Conclusion The results of the study after being given an intervention that therapy Emotional Freedom Techniq (EFT) increased the self-esteem of schizophrenic respondents in RSJD Dr. Amino Gondohutomo especially in the treatment group